The revival - Weitz, Chris 1969- (Little, Brown and company, 2016)
"A group of teens must fight against their rival gang, the Uptowners, and the adults that have survived the mysterious Sickness outside of the US"...
Keywords: Science fiction; Survival; Gangs; New York (N.Y.); Jugendbuch